STRATEGI AKTIVASI PERHATIAN DALAM PENINGKATAN MUTU PEMBELAJARAN (Pascasarjana Institut Agama Islam Almuslim Aceh, 2024)
The aims of this research to find out attention activation strategy in improving learning quality. The method was used in this this research was qualitative research by library research approach. Conclusions are drawn from the data obtained to address strategies for activating students' attention in improving the quality of learning. The research findings indicate that: 1) Attention activation strategies in improving the quality of learning can be achieved through audiovisual means. 2) Some common steps teachers take to engage students' attention through audiovisual methods include selecting appropriate media, integrating them with the curriculum, using interactive media, employing diverse media, storytelling through media, facilitating discussions, and providing active feedback.